2014
DOI: 10.1186/s12913-014-0598-x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of hip and knee osteoarthritis management in primary health care in a Norwegian county: a cross-sectional survey

Abstract: BackgroundOsteoarthritis (OA) is one of the most common causes of pain and disability in the adult population. Several studies have documented discordance between general practioners (GP) practice and management recommendations, but there is limited published information about patient reported experience of quality of care. The primary aim of this study was to assess the patient perceived quality of OA management in primary health care. Secondly, we wanted to explore the factors associated with the perceived q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 16 publications
3
28
3
Order By: Relevance
“…This study used 14 indicators to measure the quality of primary care for OA, and the data on quality were obtained using patient interview and medical records. We found that the mean QI achievement rate was 74%, which is higher than the findings in other studies [17,18,19]. The achievement rates or pharmacological treatment was lower than in the other studies [19].…”
Section: Discussioncontrasting
confidence: 76%
“…This study used 14 indicators to measure the quality of primary care for OA, and the data on quality were obtained using patient interview and medical records. We found that the mean QI achievement rate was 74%, which is higher than the findings in other studies [17,18,19]. The achievement rates or pharmacological treatment was lower than in the other studies [19].…”
Section: Discussioncontrasting
confidence: 76%
“…Despite the evidence supporting TJA rehabilitation for improved patient outcomes and the availability of best practice recommendations [30], marked variations in clinical practice have also been documented by others [1921, 31]. Because of documented variation in practice, others have advocated that quality assessment of health care, including rehabilitation, should be systematically assessed and evaluated [32]. It should be acknowledged, however, that practice variation at the therapist level is affected by macro level factors including the healthcare structure, financial reimbursement schemes, human resources and cultural influences [19].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of OA continues to increase as the population ages; this condition is also known as degenerative arthritis or senescent arthritis (Rahimzadeh et al, 2014). In China, approximately 60% of aged people suffer from OA, which severely affects their quality of life (Grønhaug et al, 2014). OA is induced by various factors including the age, joint strain, trauma, and weight gain, all of which lead to articular cartilage damage and further cause reactive hyperplasia of articular edge and subchondral bones.…”
Section: Introductionmentioning
confidence: 99%